Konsep operasi hitung metode permainan kucing-kucing - Sari, Dea Julita; Asmara, Adi; Masri, Masri (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
The aim of this research is to identify the elements of integer counting operations contained in the cat-cat game and to clarify its contribution in the context of mathematics education and preserving local culture. The method in this research is a qualitative descriptive approach with data collection carried out through direct observation during the game and focusing on player interactions and the strategies used when playing the kucing-kucing game. The results of the research show that the cat-cat game contains elements of the concept of integer counting operations, namely multiplication, division, addition and subtraction (Kabataku), especially related to the rules of the game using 12 cat-cats and a tennis ball as the tools used in the game. This makes a significant contribution in the context of mathematics education, showing the potential of traditional games as a meaningful learning resource. This research emphasizes the importance of maintaining and introducing traditional games in efforts to preserve cultural heritage and provide interesting learning alternatives for students.